Faktor Evaluasi Usabilitas dalam Sistem e-learning dengan Panduan Tinjauan Sistematik PRISMA: Indonesia - Indah Permatasari; Peny Meliaty Hutabarat; Evi Purnamasari (J-ENSITEC, 2023)
The usability evaluation of e-learning system is an important stap to understanding the quality of the interaction between the user and the system in supporting the learning process. To understan the current approaches, a systematic review was condusted using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) guidelines. A systematic review was carried out on 6 (six) scientific databases within a certain publication period. After applying various exclusion criteria, there were fifteen documents for further analysis. An analysis of the full text of the selected articles was conducted to see the approach used in evaluating the usability of the e-learning system. The author found as many as 51 factors that became criteria in assessing the usability of e-learning systems. In general, the various existing approaches refer to the two basic approaches that have been offered by previous researchers. The latest approaches in assessing the usability of e-learning systems are still modifications and adjustments from the approaches that have been proposed previously. Modifications were made to adapt to the evaluation context and use of the studied e-learning system.